2021
DOI: 10.3390/educsci11070329
|View full text |Cite
|
Sign up to set email alerts
|

Using Robots with Storytelling and Drama Activities in Science Education

Abstract: Storytelling and drama are well-known teaching tools that can be used throughout the curriculum for the active participation of students in their own learning process. The introduction of robots in storytelling and drama activities provides students with a meaningful, multisensory, hands-on learning experience. This paper explores the potential and challenges of using storytelling and drama activities with robot actors in science teaching. We present the lessons learned from two experiences of storytelling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 39 publications
2
6
0
1
Order By: Relevance
“…These results showed a significant improvement in reading skills through storytelling. This result corroborates what Bravo et. al (2021) affirmed.…”
Section: Discussionsupporting
confidence: 93%
“…These results showed a significant improvement in reading skills through storytelling. This result corroborates what Bravo et. al (2021) affirmed.…”
Section: Discussionsupporting
confidence: 93%
“…In [26], experiments were conducted with school students in the purpose of identifying methodologies of implementing storytelling and drama activities using robots in science education. It was observed that these methodologies facilitate the teacher's development of scientific concepts with students and that the presence of robots improved the classroom's environment and the students' attention.…”
Section: Storytellingmentioning
confidence: 99%
“…The Ministry of Education, educators, and schools could work together to develop programs or curricula related to resilience and character education to help students learn how to respond to and cope with potential harms and adversity, thus enhancing students’ resilience and character strength [ 73 , 74 , 75 ]. For example, storytelling and drama could be incorporated into character or resilience education [ 76 , 77 , 78 ]. Students could absorb values by listening to or retelling stories.…”
Section: Practical Implicationsmentioning
confidence: 99%